Analysis of Differences in the Serum Levels of Various Vitamins During Pregnancy: Effects of Gestational Stage and Age - Fangyuan Zheng; Pei He (Clinical and Experimental Obstetrics & Gynecology)
Background: Pregnant women exhibit an increased demand for nutrients, including vitamins, and a deficiency in vitamins can increase the risk of various pregnancy-related diseases. This study aims to evaluate the vitamin levels in women of different age groups and gestational stages in order to provide targeted dietary guidance and vitamin supplementation strategies. Methods: Pregnant women who registered and attended regular prenatal check-ups at Hangzhou Women’s Hospital from January to December 2021 were selected as study participants. Ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) was used to quantitatively determine the concentrations of vitamins A, D, E, K, B1, B2, B9 (folic acid), and B12 in the serum. Results: The serum vitamin A, B1, and B9 levels decreased with gestational age in the age-matched group, while the vitamin E level increased slightly (p < 0.05). In the advanced-aged group, the levels of vitamins A, B1, B2, and B9 decreased with gestational age, but the levels of vitamins D3, E, K, and B12 slightly increased (p < 0.05). In mid-pregnancy, age-matched women had slightly greater serum levels of vitamins E and K than did women in the advanced-aged group (Z = –2.67, p = 0.008; Z = –2.46, p = 0.014). In late pregnancy, significant differences existed in the serum levels of vitamins B2 and B12 between the two age groups (Z = –2.67, p = 0.008; Z = –2.50, p = 0.013). Conclusions: Vitamin levels varied by gestational stage and age during pregnancy, suggesting that vitamin supplementation should be individualized and stage-adjusted to improve maternal and child health.